Knowledge of readings in the Qur’an science books through online resources - Yousef A. Baker, El-Ebiary; Moslim Saeed, M. Al-Othaimin; Mohamed Ataalla, Elazab Ali Ismail (2020)
The Internet is one of the most technological means used in the current era, because of its various benefits in all fields and levels. The benefits of the Internet are many and varied. Where this technology was able to unite the world and make it connected with each other day and night; Nor did one of the divine books receive the same service and care as the book of God. The Ummah’s efforts in serving the Noble Qur’an have been concerted - for some time - reading, reading and composing, and the arts varied in this, the most prominent of which is the art of readings, where writing has been active since a very early time. Some inquisitors take it back to the end of the first century. The authors of Qur’an sciences have had great efforts in dealing with the topic of readings in their books, and hence this research came with a study focused on comparing four books of (The proof in the sciences of the Qur’an by al-Zarkashi, perfection in the sciences of the Qur’an by al-Suyuti, the increase and charity in the sciences of the Qur’an by Ibn Aqeelah al-Makki, Manahel al-Irfan in the sciences of the Qur’an by al-Zarqani). And also through the resources available on the Internet